Large Increase in the Second‐Order Nonlinear Optical Activity of a Hemicyanine‐Incorporating Zeolite Film1. Issue 21 (18th April 2013) - Pham, Tung Cao Thanh; Kim, Hyun Sung; Yoon, Kyung Byung
<x xml:space="preserve">Abstract</x> Nonlinear optics: A hemicyanine‐incorporating silicalite‐1 film with second‐order nonlinear optical properties supported on a glass plate was prepared. For the nonlinear optical properties of this material the number of hemicyanine dye moleclues included in the zeolite channels is important. Defects arising from Si deficiency along the channels prohibit the diffusion of the dyes into the interior of the zeolite film (see picture).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>